An overview of the protection of rights of unborn child under Islamic Law and the Law in Malaysia - Mohd, Azizah; Mohamed, Duryana; Baharudin, Mohammad Hidir (2018)
Issues on induced abortion and abandonment of fetus are not seemed only to trigger Malaysians but the world at large. Such issues are not seemed to be new but went back to the past several decades i.e. before the recognition of rights of unborn babies to be protected and safeguarded by the United Nations Declaration of the Rights of the Child in 1959. This is evident when The UNDRC 1959 declares that the child needs special safeguards and care, including appropriate legal protection, before as well as after birth. Unborn babies can be simply and generally understood as babies who are conceived and not yet born regardless of the terms of pregnancy. This paper mainly seeks to examine rights of unborn child under Islamic law (the Shari’ah). Under Islamic law, rights are well defined and guaranteed to all categories of human beings regardless of their stages of life, so long as it is within the purview of the Sharia’h. As regards babies and children, protection of their rights begins at the very initial stage of their life i.e. before their birth. The research is based on the hypothesis that Islam is a comprehensive way of life and govern comprehensive rules on child protection. Examination extends to the law in Malaysia especially on the issue of adequate protection of rights of unborn child. The research will adopt a qualitative methodology. The findings of the research will provide a strong theoretical framework on rights of unborn child under Islamic law, so as to provide a sample for protection of rights of unborn child. Finally, the paper will suggest improvement to the law in Malaysia where relevant and appropriate.